APPLYING AUDIO LINGUAL METHOD IN ENGLISH LESSONS - Shamsiddinovna, Ibragimova Dildora (International Journal of Psychosocial Rehabilitation, 2020)
The beneficial of technique in teaching assists the students to enjoy the learning process. The effective technique of teaching in the learning process can be seen on the performance or the goal. The goal of learning foreign language is mastered the target language. In a general way, the foreign language like English is studied by the learner in the secondary school. The technique of teaching has been made to reduce the failures of learning foreign language.Speaking and listening are important skills in learning English. Due to the significant of speaking and listening itself, there are some functions of speaking and listening for the users and respondents. The functions of those can be seen clearly in the application of speaking in daily life such as to communication, express the idea orally, give command to the other persons, etc. In addition, the method of learning speaking and listening must be taken in the learning process to achieve the goal of learning foreign language.Based on the previous explanation, it is intriguing to find out the method that it is appropriated with the technique of teaching speaking and listening. However, there are many methods of teaching speaking such as The Direct Method, Audio Lingual Method, The Grammar Translation Method, etc. Therefore, this paper will focus on the application of Audio Lingual Method in English speakingclass.